Thirty girls [large type] - Minot, Susan (Thorndike Press, a part of Gale, Cengage Learning, 2014)
Esther is a Ugandan teenager abducted by the Lord's Resistance Army and forced to witness and commit unspeakable atrocities, who is struggling to survive, to escape, and to find a way to live with what she has seen and done. Jane is an American journalist who has traveled to Africa, hoping to give a voice to children like Esther and to find her center after a series of failed relationships. Minot interweaves their stories, giving us portraits of two extraordinary young women confronting displacement, heartbreak, and the struggle to wrest meaning from events that test them both in unimaginable ways.